Discovery Learning Assisted E-Learning to Improve Student Conceptual Understanding About Heat and Its Application - Zainul Mustofa (SEAMEO QITEP in Science, 2021)
Synchronizing the concepts of heat and heat transfer explicitly on the competency of expertise in vocational schools still needs further research. This research focuses on the impact of discovery learning assisted by e-learning in improving Student Understanding about concept of heat, its transfer, and its application. Through the one-group, pretest-posttest design with 36 subjects of computer and network engineering students, Al Munawwariyyah Vocational School, this research was applied. The results showed an increase in conceptual understanding with n-gain values ​​of 0.79 (high) and a d-effect size of 3.01 (very high). This value indicates that discovery learning assisted by e-learning has a positive impact on increasing students' conceptual understanding from an average pretest of 39.9 to an average posttest of 84.1. Students' skills in troubleshooting CPU problems increase significantly after learning. Most students can explain the heat transfer by conduction, convection, and radiation that occurs on the CPU along with the impact and benefits of competency expertise.